Optimization of age and weight at first calving in dairy cattle – A way forward to enhanced productivity - Yadav, Dhawal Kant; Bharti, P K; Singh, Mukesh (Indian Farming, 2019)
Dairy industry in India has grown at tremendous rates since independence. Milk production has increased from 17 million tonnes in 1950 to 165.4 million tonnes (DAHDF Annual report, 2017-18). The per capita availability of milk has been increased from 130 g/day to 355 g/day during the same period of time, which is higher than the world average of 293.7 g. Currently, India is having 2nd largest population of cattle and highest milk production (ranks 1st)in the world due to large buffalo population. In spite of highest milk production, the productivity per animal is very low in our country due to shortage of fodder and lack of sound managerial practices. In addition, India has large proportion of non – descript cattle population which have long age at first calving and shorter productive life which needs to be upgraded by breeding with bulls of high genetic merit. Crossbreds developed in the country have exhibited better results than the indigenous breeds and even better than the exotic breeds due to enhanced heat tolerance, which can be attributed to the presence of indigenous blood.